UKURAN PERUSAHAAN MEMODERASI DETERMINAN AUDIT DELAY - Maharsa, Agustinus Guntur; Darminto, Dwi Prastowo; Merawati, Endang Etty (Jurnal Riset Akuntansi, 2021)
Abstract The time span between the issuance date of the audit report and the closing date of the financial year is called the audit delay. This study aims to examine the effect of good corporate governance represented by the board of commissioners and audit committee, leverage, auditor switching, profitability, on audit delay with company size as a moderating variable. This research was conducted at trade service and investment companies listed on the Indonesia Stock Exchange in 2015-2019. The number of samples was selected by purposive sampling method is 268 samples from 56 companies for five years. The type of data used is secondary data in the form of financial statements of trade service and investment companies. The data analysis technique used is Moderated Regression Analysis. The results showed that the board of commissioners and audit committee, leverage, profitability have an effect on audit delay, while auditor switching has no effect on audit delay. Company size moderates the effect of leverage and profitability on audit delay, but company size is unable to moderate the effect of auditor switching on audit delay. Keywords: good corporate governance, board of commissioners, audit committee, leverage, auditor switching, profitability, company size, audit delay